PROSPEK PARTAI ISLAM IDEOLOGIS DI INDONESIA - Shobron, Sudarno (Universitas Muhammadiyah Surakarta, 2013)
The ideological Islamic party ever got success in Indonesia in 1955. It wasrepresented by Masyumi and NU while in 1977 it was represented by UnitedDevelopment Party (PPP). But the success could not exceed the non Islamic party thatgot significant voters so that the Islamic parties still lost. The Reformation era givesnew opportunity for Islamic parties to emerge, for instance the Crescent Star Party(PBB), Justice Party (PKS) and PPP. These Islamic political parties are permitted tocompete in the general election. There are also parties that have Islamic socialorganization mass such as National Mandate Party (PAN) and National AwakeningParty (PKB). The fate of the parties is not far different from the ideological parties inthe Old Order and New Order. Accordingly there should be smart ideas to bore anideological party for exampleHizbut Tahrir Indonesia (HTI) to be the participant in thegeneral election in order that it is able to struggle the Islamic law in Indonesia, but doesthis ideological party have a good prospect? This article tries to give the answer.Key Words: Ideological parties, Islamic law, Hizbut Tahrir IndonesiaPartai Islam Ideologis pernah mengalami kesuksesan di Indonesia pada tahun1955 yang dipresentasikan oleh Masyumi dan NU, dan pada tahun 1977 oleh PartaiPersatuan Pembangunan (PPP). Namun kesuksesan tersebut tidak dapat melampauikesuksesan partai non-Islam yang mendapatkan suara cukup signifikan, sehingga partaiIslam ideologis tetap kalah.Era reformasi memberikan perluang munculnya partaiideologis atau partai yang berazaskan Islam, misalnya Partai Bulan Bintang (PBB).Partai Keadilan Sejahtera (PKS) dan PPP sendiri yang telah lolos verifikasi untukmengikuti pemilihan umum, selain partai yang memiliki basis masa organisasi massaIslam, misalnya Partai Amanat Nasional (PAN) dan Partai Kebangkitan Bangsa (PKB).Nasib partai-partai ini tidak jauh berbeda dengan partai ideologis pada masa OrdeLama dan Orde Baru.Untuk itulah perlu ada gagasan cerdas untuk menghadirkanpartai ideologis misalnya Hizbut Tahrir Indonesia (HTI) sebagai peserta pemilu yangmemperjuangkan syareat Islam di Indonesia, tetapi apakah partai ideologis ini memilikiprospek? Artikel ini akan mencoba memberikan jawaban.Kata Kunci: Partai Ideologis, syareat Islam, Hizbut Tahrir Indonesia